Training on Developing Digital Learning Modules for Students in the Era of Educational Transformation - Sri Utami; Ambarwati Akib; Nurul Chalisa Majiding; Dwi Utami; Magfirah Wahyu Ramadhani (Outline Publisher, 2026)
This community service activity addressed the need to strengthen the ability of Accounting Education students at Universitas Negeri Makassar to design digital learning modules that are relevant to the ongoing transformation of education. Many students are familiar with digital tools for learning, yet they still require structured guidance to develop teaching materials that are systematic, interactive, and suitable for classroom use. The activity aimed to improve students’ understanding of digital learning modules and to train them to produce initial module drafts based on accounting learning topics. The program was conducted on April 6, 2026, in a classroom setting and involved 70 students. The implementation used a participatory training approach through material presentation, demonstration, guided practice, discussion, and mentoring. The results showed that the activity increased students’ understanding of the structure and function of digital learning modules and encouraged active participation throughout the training process. Students were able to develop initial digital module drafts and demonstrated greater confidence in integrating pedagogical and digital elements into learning materials. In conclusion, the training contributed positively to the development of students’ academic and professional readiness and can be further expanded through follow-up mentoring, product refinement, and classroom-based implementation.